1997
DOI: 10.1161/01.cir.96.1.358
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Bacterial Endocarditis

Abstract: Major changes in the updated recommendations include the following: (1) emphasis that most cases of endocarditis are not attributable to an invasive procedure; (2) cardiac conditions are stratified into high-, moderate-, and negligible-risk categories based on potential outcome if endocarditis develops; (3) procedures that may cause bacteremia and for which prophylaxis is recommended are more clearly specified; (4) an algorithm was developed to more clearly define when prophylaxis is recommended for patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
21

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 358 publications
(88 citation statements)
references
References 52 publications
1
66
0
21
Order By: Relevance
“…AHA guidelines have long proposed that maintaining oral health may be important in the overall effort to prevent IE, 67,69 and there is increasing support from studies that report a frequent occurrence of bacteremia with toothbrushing (39%-46%). 42,55,68 It has also been suggested that chewing food may result in bacteremia, but there are no studies to confirm this in children.…”
Section: Impact Of Oral Disease and Hygiene Versus Dental Procedures mentioning
confidence: 99%
“…AHA guidelines have long proposed that maintaining oral health may be important in the overall effort to prevent IE, 67,69 and there is increasing support from studies that report a frequent occurrence of bacteremia with toothbrushing (39%-46%). 42,55,68 It has also been suggested that chewing food may result in bacteremia, but there are no studies to confirm this in children.…”
Section: Impact Of Oral Disease and Hygiene Versus Dental Procedures mentioning
confidence: 99%
“…Риск развития ИЭ увеличивается при наличии митральной регургитации любого генеза за счет повреждающего воздействия на клапаны так назы-ваемых "срезающих сил" (shear forces), обусловлен-ных патологическим током крови и его турбулент-ностью в районе створок [17,18]. Кальцификация кольца митрального клапана, часто наблюдающаяся у пожилых лиц и почему-то среди женщин, также является дополнительным фактором риска развития ИЭ [18][19][20][21][22][23].…”
Section: факторы рискаunclassified
“…Vor Herzkatheteruntersuchungen oder elektrophysiologischen Untersuchungen (EPU) ist eine routinemäßige antibiotische Prophylaxe nicht notwendig [9]. Eine antibiotische Abschirmung bei der Anlage zentralvenöser Zugänge erbringt keine Vorteile im Sinne einer Reduktion katheterassoziierter Bakteriämien [38].…”
Section: Patienten Mit Klappenersatzunclassified